An overview of real-world study in clinical transfusion - GONG Jiashun; LIU Fengxia; HUANG Xueyuan; DONG Hang; DU Chunhong; WANG Juan; HUANG Rong; GUI Rong (Zhongguo shuxue zazhi)
Real-world study (RWS), based on multi-source data from real medical environments, is gradually becoming an important supplement to traditional randomized controlled trials, and its application in the field of transfusion medicine is becoming increasingly widespread. This article systematically reviews the definition and methodological system of RWS, examines its application cases in clinical blood transfusion research, and discusses the advantages, limitations, and future research directions of RWS, aiming to provide a reference for evidence-based research in blood transfusion medicine.